2020
DOI: 10.3389/fphar.2020.558629
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling Reveals the Amelioration Effect of Methotrexate on Imiquimod-Induced Psoriasis in Mouse

Abstract: Background: The imiquimod (IMQ)-induced psoriasis mouse model has been used as a model for pathogenic mechanism research, and methotrexate (MTX) is widely employed to treat various clinical manifestations of psoriasis. We explored the underlying pathogenesis of psoriasis and the treatment mechanism of the conventional drugs from the metabolic perspective of the psoriasis mouse model. Methods: Male BALB/c mice were smeared IMQ for 7 days to induce treatment-resistant psoriasis and intragastrically administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The results support research conducted by Luliana in 2017, which stated that ciplukan herbal water extract has anti-inflammatory activity at a dose of 400 mg/kgBW, which also mentioned that the increased dose of ciplukan herbal water extract would increase antiinflammatory effects (Luliana et al, 2017). These results are also in line with Zong's research in 2020, which stated that MTX can improve psoriasis lesions in the form of an erythema, thickening of the skin, and squama in male BALB/c mice when applied to imiquimod (IMQ) for seven days (Zong et al, 2020).…”
Section: Resultssupporting
confidence: 67%
“…The results support research conducted by Luliana in 2017, which stated that ciplukan herbal water extract has anti-inflammatory activity at a dose of 400 mg/kgBW, which also mentioned that the increased dose of ciplukan herbal water extract would increase antiinflammatory effects (Luliana et al, 2017). These results are also in line with Zong's research in 2020, which stated that MTX can improve psoriasis lesions in the form of an erythema, thickening of the skin, and squama in male BALB/c mice when applied to imiquimod (IMQ) for seven days (Zong et al, 2020).…”
Section: Resultssupporting
confidence: 67%
“…Finally, PyMOL software was further used to visualize the results of molecular docking. The IMQ-induced psoriasis mouse model was established as described in the previous study (Qin et al, 2014;Zong et al, 2020). 48 mice were randomly divided into 6 groups, with 8 mice in each group.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…PsA is a severe form of arthritis with joint deformities and damage, present in approximately 30 % of patients with psoriasis [4,5]. The crosstalk between genetic and environmental factors (e.g., diet and lifestyle) is responsible for psoriasis by contributing to immunological abnormalities and epidermal proliferation [6]. Large-scale genome-wide association studies in multiple populations have identified approximately 80 genetic loci associated with psoriasis susceptibility [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%